Measurement of Corporate Social Responsibility of Financial Companies in the Indian Context - Sachdeva, Sakshi; Ramesh, Latha; Mathew, Mareena; K. S., Manu (Indian Journal of Finance, 2023)
Purpose : This study aimed to measure the corporate social responsibility (CSR) activities of financial companies (banks and NBFCs) in India. This paper used content analysis to quantify the CSR performance of financial companies. Financial institutions loan money to businesses utilizing assets owned by saving bank account holders, thereby heightening their societal responsibility. Methodology : Data from 63 financial companies listed on the National Stock Exchange from 2014–2015 to 2020–2021 were considered. Cronbach’s alpha, descriptive statistics, and z-score test were used in this research to check the reliability and normality of the CSR scores. Findings : The results showed that private sector banks proactively participated in social activities compared to public sector banks (PSB) and non-banking financial institutions (NBFCs). Scores of CSR improved during the study period. Practical Implications : The study will allow future research because every issue and factor considered in the scale needs attention to benefit humankind’s future generations. Calculated CSR scores could be used to measure the impact on the financial performance of companies. Originality : Unlike prior research on corporate social responsibility, the current work built a model to measure the CSR of financial companies.